Validation of Lagrangian particle movement in CFD for simulating passive object transport over weirs - Kaminski, Linus; Thorenz, Carsten; Weichert, Roman; Lehmann, Boris (Journal of Coastal and Hydraulic Structures, 2025)
Validated numerical models can facilitate the investigation of passive object transport over hydraulic structures. This study aims to validate the movement of Lagrangian particles in a numerical simulation using the two-phase OpenFOAM solver interFoam, modified to include particle tracking. A simplified weir overflow was modelled both numerically and physically, and the movement of spherical particles was analysed across three scenarios with varying tailwater levels. The validation focused on particle collisions immediately after weir passage, residence times within the study area, and upstream movements in recirculation zones such as the hydraulic jump and the water cushion between the weir and the nappe. These parameters were selected because the method is intended to contribute to a better assessment of downstream fish passage over weirs. Results from the numerical and laboratory models showed a high level of agreement. Collision counts and positions, as well as particle residence times and upstream movements, exhibited consistent trends across all three scenarios. The most significant deviation was observed in the number of particles entering the water cushion. This discrepancy is attributed to limitations of the Volume of Fluid (VOF) method, particularly the smearing of the air–water interface. Thus, when employing this methodology, it is essential to account for the inherent limitations of the applied numerical simulation approach. While a perfect replication of fish passage over a weir is not achievable, the method enables reliable qualitative comparisons across different configurations. It may therefore serve as a useful tool for evaluating hydraulic conditions relevant to fish passage.